English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

answers:
ln 6
-3 ln 6
-3 + ln 6
ln 6/-3

2007-02-12 05:02:12 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

e^x+3=6

Taking natural logs of both sides yield

x+3=ln 6

Therefore x=-3+ln 6

2007-02-12 05:07:07 · answer #1 · answered by The exclamation mark 6 · 0 0

This is open to some interpretation:
If e^x+3=6
subtract 3 from both sides
to get e^x = 3 and x = ln 3.
If x+3 is your exponent
then x+3 = ln 6
and x = -3 + ln 6.

2007-02-12 13:10:59 · answer #2 · answered by steiner1745 7 · 0 0

ln 6

2007-02-12 13:05:51 · answer #3 · answered by camus140 2 · 0 2

Looking at the possible answers it seems that the exponent is
(x+3)
so if e^(x+3) =6 x+3 = ln6 and x= -3 +ln6 (The last one)

2007-02-12 13:10:43 · answer #4 · answered by santmann2002 7 · 0 0

Assume what is meant is e ^ (x+3) = 6
(x + 3) log e = log 6
x log e + 3 log e = log 6
x = log 6 - 3 log e
x = log 6 - 3 which is 3rd answer.

2007-02-12 13:21:16 · answer #5 · answered by Como 7 · 0 0

fedest.com, questions and answers